Ad ripam fluminis Danuvi Papers of the 3rd International Conference on the Roman Danubian Provinces, Vienna, 11th-14th November 2015 (2021)
The volume contains 29 papers presented at the 3rd International Conference on the Roman Danubian Provinces, Vienna, 11th-14th November 2015. These contributions represent the fields of Ancient History, Greek and Latin Epigraphy as well as Archaeology. The main focus of the volume lies in the historical analysis of inscribed monuments.